2019
DOI: 10.1177/0022429419844508
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Choir Spacing and Riser Step Heights on Acoustic and Perceptual Measures of SATB Choir Sound Acquired From Four Microphone Positions in Two Performance Halls

Abstract: We assessed the effects of singing in two venues on acoustic and perceptualmeasures of performances by an SATB choir ( N = 28) as it sang in three spacing conditions, on two different riser unit heights, with data acquired from four microphone locations in each hall. Among primary acoustic results, long-term average spectra measures yielded a systematic pattern of significant contrasts between close and spread spacing conditions, with decreasing high-frequency energy as space between singers increased, regardl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Singers were laterally spaced using dowel rods measuring 0.61 m (24 in.) so that intersinger distance remained consistent (Daugherty, 1999(Daugherty, , 2003Daugherty et al, 2013Daugherty et al, , 2019. We projected a conductor video, of the choir's usual conductor demonstrating a pattern and tempo similar to that of the previous performance, on the back wall of the recital hall as to not impede microphone placement.…”
Section: Choir Recording Session Proceduresmentioning
confidence: 99%
“…Singers were laterally spaced using dowel rods measuring 0.61 m (24 in.) so that intersinger distance remained consistent (Daugherty, 1999(Daugherty, , 2003Daugherty et al, 2013Daugherty et al, , 2019. We projected a conductor video, of the choir's usual conductor demonstrating a pattern and tempo similar to that of the previous performance, on the back wall of the recital hall as to not impede microphone placement.…”
Section: Choir Recording Session Proceduresmentioning
confidence: 99%
“…Daugherty concluded that singer spacing may have a greater effect on choral sound than formation (e.g., mixed vs. sectional). In experiments with both auditioned and nonauditioned high school and university ensembles, he consistently found that both singers and listeners preferred spread spacing of at least 2 ft between singers over close spacing of one inch (Daugherty, 1999(Daugherty, , 2003Daugherty et al, 2013;Daugherty et al, 2019). Adams (2019a) concluded that both large and chamber university ensembles also preferred spread spacing (2 ft) over moderate (1 ft) or close Update 39 2(1 in.)…”
Section: Intrasection Singer Configurationmentioning
confidence: 99%
“…Participants wore numbered nametags and stood on color-coded markings (placed according to configuration specifications) on Wenger risers in the regular choral rehearsal room for recordings. I placed markings 2 ft (0.61 m.) apart for optimal intersinger spacing (Daugherty, 1999(Daugherty, , 2003Daugherty et al, 2013;Daugherty et al, 2019). I positioned a Roland R05 digital recorder at a standing-conductor ear height of 5 ft 4 in.…”
Section: Recording Conditionsmentioning
confidence: 99%
“…This is in line with the literature which suggests that experienced singers tend to choose spaces with different reverberation times than novices 19 . The spatial arrangement of choristers and height differences among them, which often involves risers, significantly impacts auditory perception 39 . A small group (4,5%) confirms altering choir position or even layout (4,5%) for this purpose.…”
Section: Choristers' Inquirymentioning
confidence: 99%